(untitled) (Global Journal of Science Frontier Research, 2012)
Pineapple (Ananas comosus (L.) Merr.) is an important fruit crop grown in Nigeria. Extension of the shelf life of pineapple fruits continues to be a challenge in Nigeria. The search for safe, healthy and environmental friendly treatments has led to increased interest in research into edible and biodegradable films and coatings. The aim of this study was to evaluate the effect of Aloe vera gel as an edible coating on weight loss, ascorbic acid, pH and firmness in order to extend the shelf-life of pineapple stored at ambient temperature of (27+2oC) and relative humidity of 55-60% for seven weeks. The above parameters which are related to post -harvest quality loss were however significantly controlled in the pineapple coated with A. vera gel. The storability of pineapple fruits was extended by seven weeks. It was concluded that A. vera gel used as a coating for pineapple could serve as an alternative to post - harvest chemical treatments.